Non-exudative OCT findings in neovascular AMD - Vidal Oliver, Lourdes; Fernández-Avellaneda, Pedro; Fragiotta, Serena; Corradetti, Giulia; Borrelli, Enrico; Dolz-Marco, Rosa (Eye, 2025)
In this narrative review we describe the main optical coherence tomography biomarkers appearing in eyes with neovascular age-related macular degeneration (AMD) that do not directly correspond to exudation. We highlight those signs that may mimic exudation and therefore do not require active treatment, such as outer retinal tubulations, pseudocysts, lipid globules, or hyporeflective wedges. Other signs may indicate impending exudation such as hyperreflective foci or shallow irregular retinal pigment epithelium elevation, and therefore should be carefully monitored. We also review and summarize the different origins of subretinal hyperreflective material and describe the main signs of degeneration seen in eyes with AMD, such as outer retinal tubulation, thinning of the retinal layers, outer retinal atrophy, and choroidal changes.